Inguinal abscess in twin infants - Sadhukhan, Meghmala; Mishra, Baikuntha N.; Joshi, Ranjit K.; Pahi, Prabin Prakash (International Surgery Journal, 2020)
Inguinal abscess is uncommon in infants and children. Majority of cases in the infantile period is primary and they present as leg or groin swelling, limitation of limb movement and pain. The source of microorganism is from the haematogenous spread of normal flora of the skin due to immature immune system. Ultrasound is the investigation of choice which confirms the diagnosis and delineates the areas of collection. Antibiotic alone is insufficient in most cases and drainage is required. Delayed treatment and inadequate drainage carry a high risk of mortality and sequelae due to damage to the underlying joint. We present 2 cases of primary inguinal abscess in twin infants who presented at 1 month and 2 months of age correspondingly, in whom early diagnosis and management lead to quick recovery.